Hepatic Encephalopathy in Osler-Weber-Rendu Syndrome - Sakthi Gautham; Christopher J. Haas (Annals of Internal Medicine: Clinical Cases)
Hereditary hemorrhagic telangiectasia or Osler-Weber-Rendu syndrome is a rare condition that leads to multiple vascular malformations. We describe the interesting patient case of a woman with recurrent epistaxis secondary to Osler-Weber-Rendu syndrome, who presented with confusion, and was ultimately found to have a hepatic arteriovenous malformation leading to hepatic encephalopathy. Computed tomography angiography images are provided, which highlight the extensive hepatic arterioportal shunting that caused elevated serum ammonia levels in the setting of gastrointestinal breakdown of blood products.